15(s-3)=12s-43

Simple and best practice solution for 15(s-3)=12s-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15(s-3)=12s-43 equation:


Simplifying
15(s + -3) = 12s + -43

Reorder the terms:
15(-3 + s) = 12s + -43
(-3 * 15 + s * 15) = 12s + -43
(-45 + 15s) = 12s + -43

Reorder the terms:
-45 + 15s = -43 + 12s

Solving
-45 + 15s = -43 + 12s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-12s' to each side of the equation.
-45 + 15s + -12s = -43 + 12s + -12s

Combine like terms: 15s + -12s = 3s
-45 + 3s = -43 + 12s + -12s

Combine like terms: 12s + -12s = 0
-45 + 3s = -43 + 0
-45 + 3s = -43

Add '45' to each side of the equation.
-45 + 45 + 3s = -43 + 45

Combine like terms: -45 + 45 = 0
0 + 3s = -43 + 45
3s = -43 + 45

Combine like terms: -43 + 45 = 2
3s = 2

Divide each side by '3'.
s = 0.6666666667

Simplifying
s = 0.6666666667

See similar equations:

| 5(x-6)= | | (5+4)*5+3-7+38+2*(9+1*8)= | | 9(2x+1)= | | x^4+9x^2-2x^3-18x= | | 9-2x/2=6(1-x)/3 | | 13m-4-10m=2 | | 2[7x-4]+3=51 | | -5n+6n+15-3=-3 | | 11r^2-9r+3=0 | | [x-4]-10=1 | | x*2+x-6=0 | | m^2+9m+8=0 | | 5*(5x+9)-7*(x-9)=11*(x-2) | | x^3-5x^2+3x-9=0 | | (13x-5)*5=(3+8x)*8-21 | | 0=y-9 | | y=-0-9 | | 18+5*(3x-2)=2*(7x+1) | | 32+9x=x-(2x+8) | | 10n^2+20n-8=0 | | y=.5(-2) | | 5*(9x-8)-1*(8+3x)*15=13 | | 4x+5(0)=-20 | | 4(0)+5y=-20 | | 5+y=4 | | y=x^2-12x+40 | | b^2-2b-75=0 | | 3w^2+16w+5=0 | | 3w+16w+5=0 | | y=2x^2-8x+7 | | -6-8=7x+24 | | 3b^2-6b+3=0 |

Equations solver categories